Kecepatan Pembakaran Premixed Campuran Minyak Jarak - Liquefied Petroleum Gas (LPG) pada Circular Tube Burner - Riwu, Defmit B.N.; Wardana, I.N.G.; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
This study was conducted to determine the characteristics of premixed combustion of a mixture of castor oil - LPG on a circular tube burner. Percentage of LPG fuel in a mixture of jatropha curcas oil - LPG varied as much as 10%, 20%, 30%, and 40% of the mass flow jatropha curcas oil vapor. Considering the flame of fire there are two angles formed which describe burning velocity. Also there are formed two cones of fire where the bright blue inside cone is a premixed flame, while the outer blue white cone is flame a diffusion flame. An increase in the percentage of LPG makes the value of top and bottom angle increase. So that the burning velocity on the upper angle decrease whilst on bottom angle increase.